Worst-Case tsunami inundation modeling using high-resolution UAV-DEM in various coastal typologies, case study Gunungkidul coastal area - Fatchurohman, Hendy (IOP Publishing Ltd, 2022)
A tsunami is a significant threat to the coastal community. The southern coast of Java is considered a tsunami-prone area due to its location facing the Indian Ocean. Gunungkidul Regency in Yogyakarta Special Region is well known for its attractive coastal tourism. Numerous visitors are exposed to tsunami hazards that can be occurred unpredictably. The unavailability of a reliable tsunami hazard map leads to an ineffective evacuation plan. This study aims to implement UAV data for tsunami hazard mapping in different coastal typologies. This study was conducted at Baron Beach, Drini, and Wediombo. The tsunami inundation model was generated from high-resolution UAV-DEM. The worst inundation scenario was set at 12 meters. Based on the results, Baron and Drini are considered highly susceptible to tsunami hazards due to their topographic conditions, mostly located on the flat karst valley. Wediombo is categorized as the primary coast that is formed by the volcanic process. The inundation model at Wediombo only covers a small extent of the area. Volcanic origin morphology formed an undulating to hilly topography that plays an essential role as a natural barrier for the tsunami. However, minimum access and narrow pedestrian street become serious disadvantages for tsunami evacuation route planning at Wediombo Beach. © 2022 Institute of Physics Publishing. All rights reserved.